DIFFERENCE IN FAITH AS AN ULTIMATE REASON IN SUBMITTING DIVORCE LAWSUITS IN INDONESIAN FAMILIES OF DIFFERENT RELIGIONS - Fachrian Rizki; M. Ya’kub Aiyub Kadir (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2021)
As the issuance of various Indonesian Court Decisions which permit couples of different religion to perform marriage, marriage between people of different religion becomes a common practise among the nowadays society. These families of different religions, as another families, certainly may be faced with any kinds of household problems, which in some cases lead to divorce lawsuits before District Court of their domicile. I argue that the difference in faith used as an ultimate reason in submitting divorce lawsuits before the court, whereby difference in faith said as the cause of the failure of marriage’s intention, id est to establish a happy and eternal family. In this regard, this research will be conducted by analysing and interpreting the collected data, id est Secondary Data Source which obtained through library research, in order to discover the backgrounds underlying them. Key Words: Difference in Faith, Divorce Lawsuits, Indonesian Court Decisions, Families of Different Religions.